TRAUMA, MEMORY, AND IDENTITY IN POST-WAR ENGLISH FICTION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the interconnected themes of trauma, memory, and identity in post-war English fiction. After the Second World War, English literature increasingly focused on the psychological and emotional consequences of violence, loss, and social disruption. The study examines how novelists represent trauma through fragmented narratives, unreliable memory, and complex character identities. It argues that memory functions as a central mechanism through which characters attempt to reconstruct their sense of self in the aftermath of war. By analyzing selected post-war English novels, the article demonstrates how fiction becomes a space for confronting collective and individual trauma, revealing the lasting impact of war on personal identity and cultural consciousness.